Pendampingan Penentuan Industri Unggulan dan Program Pembangunan Industri Kabupaten Solok - Prima Fithri; Alfadhlani Alfadhlani; Reinny Patrisina; Armijal Armijal (Warta Pengabdian Andalas, 2023)
The industrial development process needs to be well planned so that the process can be carried out in a systematic, comprehensive, futuristic and measurable manner. The planned national industrial development policy has been outlined in the National Industrial Development Master Plan (RIPIN) 2015-2035. Based on data from the Central Bureau of Statistics for Solok Regency in 2022, it is known that the role of the agricultural sector in the regional economy is illustrated by its contribution to the Regency's Gross Regional Domestic Product (GRDP) Solok is still very dominant, while the contribution of the industrial sector is still around 5%. Therefore the Solok Regency Industrial Development Plan is needed to accelerate the achievement of the abovementioned target. It is even hoped that it can exceed the target. In addition, it intends to have a systematic and measurable plan for achieving the future industrial development vision in Solok Regency. The Solok Regency Industrial Development Plan for 2022-2042 has been prepared with a complete study, referring to relevant documents and field visits related to community business potential and existing resource potential. Five leading industries had been determined due to a study in Solok Regency.